Upregulation of T-cadherin suppresses cell proliferation, migration and invasion of gastric cancer in vitro - Lin, Jianqing (Exp Ther Med, 2017)
As a unique member of the cadherin superfamily, T-cadherin (T-cad) has been demonstrated to be associated with gastric cancer (GC) prognosis. To elucidate the function of T-cad in GC in vitro, the present study firstly examined T-cad protein expression in normal and gastric cancer tissues and cell lines, and it was demonstrated to be significantly downregulated in gastric cancer samples compared with normal samples. Control and T-cad expression vectors were then transfected into the MGC8-03 and AGS GC cell lines. Utilizing MTT, clonogenic, flow cytometry, wound healing and Transwell invasion assays in addition to Western blotting, the present study demonstrated that the overexpression of T-cad suppressed GC cell growth and colony formation via cell cycle arrest at the G0/G1 phase via downregulating the expression of cyclin dependent kinase 4 and Cyclin D1. In addition, overexpression of T-cad significantly inhibited GC cell migration and invasion by increasing E-cadherin and decreasing Vimentin expression. These findings suggest T-cad may be important in GC cell proliferation and metastasis and serve as a promising target for the treatment of GC in the future.